Overcoming seed coat dormancy in Tephrosia bracteolata Perr..& Guill., a Fodder Legume of West African Savanna - Awodoyin, Rasheed O.; Ogunyemi, Sola; Isichei, Augustine O. (Ecological Society of Nigeria, 2014)
Haphazard field establishment due to impervious seed coat dormancy is peculiar to legumes. The effects of physical scarification (sand abrasion, clipping with scissors and pin piercing), exposure to concentrated sulphuric acid for 0, 10, 20, 30, 40 and 50 minutes. and exposure to boiling water for 0, 5, 30, 60, and 120 seconds on percentage germination and median germination time of Tephrosia bracteolata seeds were studied in Ibadan. The results showed that the three methods were effective in overcoming hard seed coat dormancy in T. bracteolata. Treatment means in all the pre-germination methods were significantly (P<0.001) different. The final percentage germination values were similar and best in 20 and 30 minutes acid exposure time, 5 seconds boiling water exposure time, and in scissors and pin piercing treatments of the physical scarification. The 20 and 30 minutes acid scarification had lowest median germination time of 0.9 days followed closely by 5 seconds boiling water scarification with 1.1 days. Overcoming the impervious seed coat dormancy in T. bracteolata will ensure its uniform seedling growth if utilised for fodder bank, grazing reserve and green manure establishment. Boiling water pre-germination treatment for 5 seconds may be adopted .for its little skill and low resource demand.